(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
In recent years, progress in information and communication technology (ICT) has caused many structural changes such as reorganization of economy, globalization, and trade extension, which leads to capital flows and enhancing information availability. Moreover, ICT plays a significant role in development of each economic sector, especially during liberalization process. Growth economists predict that economic growth is driven by investments in ICT. Information and Communication Technology (ICT) such as the world-wide application of mobile phones and internet etc. have contributed substantially to the fast-growing world economy in unprecedented ways. The objectives of this study was to identify and determine the role that ICT played/playing in improving the economic growth and development of Jigawa state, also factors limiting the use of ICT in most of the key areas that support economy are identified. A questionnaire survey was administered manually to 184 sampled respondents. Descriptive statistic were used in analyzing the data and testing of hypothesis among different classes of the respondents. The result showed that everyday more people are getting involved in using ICT technology, these tells that ICT brings positive change in diversifying the Jigawa state economy. The implications of these results are that most people of Jigawa state are doing farming as their occupation and have a disperse settlement, because of these, they requires maximum support from either government or private organizations to provide them with ICT facilities, orient the people on the use of ICT and the possible ways to use it for self-entrepreneurship program in order to boost the economy.